Clinical outcomes and complications of pancarpal arthrodesis stabilised with 3.5 mm/2.7 mm locking compression plates with internal additional fixation in 12 dogs. Issue 5 (3rd September 2019) - Tuan, J; Comas, N; Solano, M
ABSTRACT: Aims: To report the clinical outcomes and complications after the use of 3.5 mm/2.7 mm locking compression plates (LCP) with additional internal fixation for pancarpal arthrodesis (PCA) in dogs. Methods: This was a retrospective study using medical records from a single orthopaedic referral hospital between December 2015 and April 2018. The inclusion criteria were the use of a dorsally applied LCP for PCA in dogs with a minimum follow-up period of 12 months. Additional crossed 2.7 or 3.5 mm cortical screws or Kirschner wires were placed in all limbs to further stabilise the joints. A light dressing without external coaptation was applied postoperatively to all limbs. Postoperative lameness assessment was recorded at the last clinical evaluation. Results: Twelve dogs with 13 arthrodesed limbs were included, with carpal hyperextension injury being the most common indication for surgery (4/13; 31%). One dog was recorded with a minor complication, which was a metacarpal fracture distal to the bone plate. Major complications were observed in 4/13 (31%) limbs, with surgical site infection being recorded in all four limbs and screw loosening in one limb. No implant failure was reported. At the final clinical evaluation (43–437 days after surgery), none or mechanical lameness was recorded in 9/13 (69%) limbs, mild lameness in 3/13 (23%) limbs, and moderate lameness in one 1/13 (8%) limb. Conclusions and clinical relevance: Locking plate and screw fixation with additional internal fixation resulted in comparable complication and infection rates in canine PCA to previous published studies using hybrid dynamic compression plates. No implant failure was reported for any of the limbs despite the use of a light dressing without external coaptation.